Distribution of Fibrinolytic and Proteolytic Enzymes in Subcellular Fractions of Human Granulocytes - Prokopowicz, J (Thrombosis and Haemostasis, 1968)
The Cohn and Hirsch method was applied for preparation of human granulocyte subfractions. It was found that specific granules contained about 50-60% of the total activity of acid phosphatase, alkaline and acid protease. The activities of fibrinolytic enzymes (plasminogen, activator of plasminogen and spontaneous fibrinolytic activity) were rather equally distributed in all subfractions.A significant rise of a total fibrinolytic activity was found during fractionation. The results suggest the existence of a fibrinolytic inhibitor in the granulocytes. This suggestion was substantiated by analysing dilution curves of the plasminogen activity in the granulocyte subfractions.The inhibitor showed both “antiurokinase”, “antistreptokinase” and antiplasmin activity.On the basis of experimental data it has been suggested that plasma plasminogen may be derived from the granulocytes.